Does public attention reduce the influence of moneyed interests? Policy positions on SOPA/PIPA before and after the internet blackout - Ulrich Matter; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2019)
We investigate the role of public attention in determining the effect that campaign contributions by interest groups have on legislators' policy positions. We exploit the shock in public attention induced by the Internet service blackout of January 2012 that increased the salience of the SOPA/PIPA bills aimed at stronger protection of property rights on the Internet. Using a new dataset of U.S. congressmen's public statements, we find a strong statistical relationship between campaign contributions funded by the affected industries and legislators' positions. However, this relationship evaporates once the two bills become primary policy issues. Our results are consistent with the notion that legislators choose positions on secondary policy issues in order to cater to organized interests, whereas positions on primary policy issues are driven by electoral support.
Keywords: D72; L82; L86; 330; Campaign finance; public attention; outside lobbying; Internet governance; mass media; policy positions; interest groups